Acrylic rubber, rubber composition and cross-linked product thereof, and rubber hose
By adjusting the mass ratio of ethyl acrylate and n-butyl acrylate in acrylate rubber and controlling the content of toluene insoluble components, the problem of insufficient bending fatigue resistance of acrylate rubber in the prior art is solved, and higher bending fatigue resistance and tensile strength are achieved.
Patent Information
- Application Number
- CN202180006073.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-30
- Filing Date
- 2021-01-20
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2041-01-20
AI Technical Summary
In the prior art, there is still room for improvement in bending fatigue resistance of acrylate rubber, and it is difficult to meet certain high-demand application scenarios.
By adjusting the mass ratio of ethyl acrylate and n-butyl acrylate in acrylate rubber, and controlling the content of toluene insoluble components within a specific range, the bending fatigue resistance of the crosslinked substance is improved.
The bending fatigue resistance and tensile strength of the crosslinked object are significantly improved, while the moldability and cold resistance are optimized.
Smart Images

Figure BDA0003611873060000141
Abstract
Description
Technical Field
[0001] The present invention relates to an acrylic rubber, a rubber composition and a cross-linked product thereof, and a rubber hose. Background Art
[0002] Acrylic rubber and its crosslinked products are widely used as materials for hose parts in automobile engine chambers, etc., due to their excellent physical properties such as heat resistance, oil resistance, and mechanical properties. One of the properties required of such crosslinked products of acrylic rubber is that cracks are not easily generated when the crosslinked product is bent (referred to as bending fatigue resistance). For example, Patent Document 1 discloses an acrylic rubber composition having a specific anti-aging agent, carbon black, and a crosslinking agent added to acrylic rubber as an acrylic rubber composition capable of providing a crosslinked product having excellent bending fatigue resistance.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2012-211239 Summary of the invention
[0006] Problems to be solved by the invention
[0007] In Patent Document 1, bending fatigue resistance is improved by setting the acrylic rubber composition to a specific composition. However, according to the research conducted by the inventors of the present application, there is room for improvement in the acrylic rubber itself for improving the bending fatigue resistance.
[0008] Therefore, an object of one aspect of the present invention is to provide an acrylic rubber capable of improving the bending fatigue resistance of a cross-linked product.
[0009] Means for solving problems
[0010] The inventors of the present application have found that, in an acrylic rubber containing ethyl acrylate and n-butyl acrylate as monomer units, by setting the mass ratio of the content of ethyl acrylate to the content of n-butyl acrylate and the content of toluene-insoluble components contained in the acrylic rubber within a predetermined range, the bending fatigue resistance of a cross-linked product can be improved compared with a case where the mass ratio and the content of toluene-insoluble components are outside the predetermined range.
[0011] One aspect of the present invention is an acrylic rubber comprising ethyl acrylate and n-butyl acrylate as monomer units and a toluene-insoluble component, wherein the mass ratio of the content of ethyl acrylate to the content of n-butyl acrylate is 2 or more, and the content of the toluene-insoluble component is 5 mass % or less based on the total amount of the acrylic rubber.
[0012] The acrylate rubber may contain methacrylate as a monomer unit. The acrylate rubber may further contain ethylene as a monomer unit. The acrylate rubber may further contain a crosslinking point monomer having a carboxyl group as a monomer unit.
[0013] The acrylic rubber may contain only ethyl acrylate, n-butyl acrylate, ethylene, and a cross-linking point monomer having a carboxyl group as monomer units. In this case, the content of ethyl acrylate may be 70 to 90% by mass based on the total amount of monomer units. The content of n-butyl acrylate may be 10 to 30% by mass based on the total amount of monomer units. The content of ethylene may be 0.5 to 5% by mass based on the total amount of monomer units. The content of the cross-linking point monomer may be 0.5 to 5% by mass based on the total amount of monomer units.
[0014] Another aspect of the present invention is a rubber composition containing the above-mentioned acrylic rubber. Another aspect of the present invention is a cross-linked product of the rubber composition. Another aspect of the present invention is a rubber hose comprising the cross-linked product.
[0015] Effects of the Invention
[0016] According to one aspect of the present invention, an acrylic rubber capable of improving the bending fatigue resistance of a cross-linked product can be provided. DETAILED DESCRIPTION
[0017] One embodiment of the present invention is an acrylic rubber containing ethyl acrylate and n-butyl acrylate as monomer units.
[0018] From the viewpoint of improving the tensile strength of a crosslinked product of an acrylic rubber (composition containing acrylic rubber) (hereinafter also referred to as a "crosslinked product"), the content of ethyl acrylate is preferably 70% by mass or more, 72% by mass or more, 74% by mass or more, or 76% by mass or more, based on the total amount of monomer units contained in the acrylic rubber. From the viewpoint of improving the cold resistance of the crosslinked product, the content of ethyl acrylate is preferably 90% by mass or less, 87% by mass or less, 85% by mass or less, or 82% by mass or less, based on the total amount of monomer units contained in the acrylic rubber. The content of ethyl acrylate based on the total amount of monomer units contained in the acrylic rubber may be 70-90 mass%, 70-87 mass%, 70-85 mass%, 70-82 mass%, 72-90 mass%, 72-87 mass%, 72-85 mass%, 72-82 mass%, 74-90 mass%, 74-87 mass%, 74-85 mass%, 74-82 mass%, 76-90 mass%, 76-87 mass%, 76-85 mass%, or 76-82 mass%.
[0019] The total content of ethyl acrylate and n-butyl acrylate, based on the total amount of monomer units contained in the acrylic rubber, may be 90% by mass or more, 93% by mass or more, 95% by mass or more, or 96% by mass or more; may be 99.5% by mass or less, or 99% by mass or less; or may be 90-99.5% by mass, 90-99% by mass, 93-99.5% by mass, 93-999% by mass, 95-99.5% by mass, 95-99% by mass, 96-99.5% by mass, or 96-99% by mass.
[0020] From the viewpoint of improving the cold resistance of the crosslinked product, the content of n-butyl acrylate is preferably 10% by mass or more, 12% by mass or more, or 15% by mass or more, based on the total amount of monomer units contained in the acrylic rubber. From the viewpoint of improving the tensile strength of the crosslinked product, the content of n-butyl acrylate is preferably 30% by mass or less, 25% by mass or less, or 22% by mass or less, based on the total amount of monomer units contained in the acrylic rubber. The content of n-butyl acrylate can also be 10-30% by mass, 10-25% by mass, 10-22% by mass, 12-30% by mass, 12-25% by mass, 12-22% by mass, 15-30% by mass, 15-25% by mass, or 15-22% by mass, based on the total amount of monomer units contained in the acrylic rubber.
[0021] The mass ratio of the content of ethyl acrylate to the content of n-butyl acrylate in the monomer unit (content (mass) of ethyl acrylate / content (mass) of n-butyl acrylate) is 2 or more from the viewpoint of improving the bending fatigue resistance of the cross-linked product, and is preferably 2.1 or more, 2.2 or more, 2.3 or more, 2.5 or more, 3 or more, 3.5 or more, 3.8 or more, 4 or more, or 4.1 or more from the viewpoint of further improving the bending fatigue resistance of the cross-linked product and also improving the tensile strength of the cross-linked product. From the viewpoint of improving the cold resistance of the cross-linked product, the mass ratio is preferably 12 or less, 11 or less, 10 or less, 8 or less, 6 or less, or 5 or less.
[0022] The acrylic rubber further contains ethylene as a monomer unit. Based on the total amount of monomer units contained in the acrylic rubber, the content of ethylene can be 0.5% by mass or more, 0.7% by mass or more, or 1% by mass or more, and can be 5% by mass or less, 4% by mass or less, or 3% by mass or less. Based on the total amount of monomer units contained in the acrylic rubber, the content of ethylene can be 0.5-5% by mass, 0.5-4% by mass, 0.5-3% by mass, 0.7-5% by mass, 0.7-4% by mass, 0.7-3% by mass, 1-5% by mass, 1-4% by mass, or 1-3% by mass.
[0023] The acrylic rubber may further contain a crosslinking monomer having a carboxyl group as a monomer unit. The crosslinking monomer is a monomer that can be copolymerized with ethyl acrylate and n-butyl acrylate and has a carboxyl group for forming a crosslinking point (also referred to as a crosslinking site). The crosslinking monomer has a polymerizable carbon-carbon double bond, such as an acryloyl group, a methacryloyl group, an allyl group, a methallyl group, a vinyl group, or an alkenylene group.
[0024] Examples of the cross-linking point monomer having a carboxyl group include acrylic acid, methacrylic acid, crotonic acid, 2-pentenoic acid, maleic acid, fumaric acid, itaconic acid, and maleic acid monoalkyl esters.
[0025] The content of the crosslinking point monomer may be 0.5% by mass or more, 0.7% by mass or more, or 1% by mass or more, and may be 5% by mass or less, 4% by mass or less, or 3% by mass or less, based on the total amount of monomer units contained in the acrylic rubber. The content of the crosslinking point monomer may be 0.5-5% by mass, 0.5-4% by mass, 0.5-3% by mass, 0.7-5% by mass, 0.7-4% by mass, 0.7-3% by mass, 1-5% by mass, 1-4% by mass, or 1-3% by mass, based on the total amount of monomer units contained in the acrylic rubber.
[0026] The acrylic rubber may further contain other monomers other than the above-mentioned monomers as monomer units.
[0027] Examples of other monomers include alkyl acrylates other than ethyl acrylate and n-butyl acrylate, alkyl methacrylates, alkoxyalkyl (meth)acrylates, fluorine-containing (meth)acrylates, hydroxyl-containing (meth)acrylates, tertiary amino group-containing (meth)acrylates, alkyl methacrylates, alkyl vinyl ketones, vinyl ethers, allyl ethers, aromatic vinyl compounds, vinyl nitriles, vinyl halides, and vinylidene halides.
[0028] Examples of the alkyl acrylate other than ethyl acrylate and n-butyl acrylate include methyl acrylate, n-propyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, 2-methylpentyl acrylate, n-octyl acrylate, and 2-ethylhexyl acrylate. Examples of the alkyl methacrylate include methyl methacrylate and octyl methacrylate.
[0029] Examples of the alkoxyalkyl (meth)acrylate include 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-(n-propoxy)ethyl (meth)acrylate, 2-(n-butoxy)ethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 2-(n-propoxy)propyl (meth)acrylate, and 2-(n-butoxy)propyl (meth)acrylate.
[0030] Examples of the fluorine-containing (meth)acrylate include 1,1-dihydroperfluoroethyl (meth)acrylate, 1,1-dihydroperfluoropropyl (meth)acrylate, 1,1,5-trihydroperfluorohexyl (meth)acrylate, 1,1,2,2-tetrahydroperfluoropropyl (meth)acrylate, 1,1,7-trihydroperfluoroheptyl (meth)acrylate, 1,1-dihydroperfluorooctyl (meth)acrylate, and 1,1-dihydroperfluorodecyl (meth)acrylate.
[0031] Examples of the hydroxyl group-containing (meth)acrylate include 1-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and hydroxyethyl (meth)acrylate. Examples of the tertiary amino group-containing (meth)acrylate include diethylaminoethyl (meth)acrylate and dibutylaminoethyl (meth)acrylate.
[0032] Examples of alkyl vinyl ketones include methyl vinyl ketone. Examples of vinyl ethers include vinyl ethyl ether. Examples of allyl ethers include allyl methyl ether. Examples of aromatic vinyl compounds include styrene, α-methylstyrene, chlorostyrene, and vinyltoluene. Examples of vinyl nitriles include acrylonitrile and methacrylonitrile. Examples of vinyl halides include vinyl chloride and vinyl fluoride. Examples of vinylidene halides include vinylidene chloride and vinylidene fluoride.
[0033] The content of other monomers may be 1% by mass or more and 10% by mass or less based on the total amount of monomer units contained in the acrylic rubber.
[0034] The acrylic rubber preferably does not contain methacrylic acid ester as a monomer unit. The acrylic rubber more preferably contains only ethyl acrylate, n-butyl acrylate, ethylene, and a crosslinking point monomer having a carboxyl group as monomer units.
[0035] The acrylic rubber can be obtained by copolymerizing the above-mentioned monomers by a known method such as emulsion polymerization and suspension polymerization. More specifically, the acrylic rubber can be obtained by, for example, the following method.
[0036] First, a monomer mixture containing ethyl acrylate and n-butyl acrylate and an aqueous solution of an emulsifier (e.g., an aqueous solution of polyvinyl alcohol) are mixed in a reaction container to prepare a suspension. Next, after replacing the reaction container with nitrogen, ethylene is pressed into the reaction container at a pressure of, for example, 0.5 to 5 MPa as required. Thereafter, while stirring the suspension, a polymerization initiator is added to the suspension to start polymerization, for example, at 40 to 100° C. for 1 to 24 hours. A coagulant (e.g., an aqueous solution of sodium borate) is added to the obtained copolymer to solidify the copolymer, and then the steps of washing the copolymer with water, dehydrating and drying are sequentially performed to obtain an acrylic rubber. In the case of obtaining an acrylic rubber by such a method, the method of mixing the monomer mixture with the aqueous solution of an emulsifier to prepare a suspension in advance tends to reduce the toluene-insoluble components described later, compared with the method of mixing the aqueous solution of an emulsifier to prepare a suspension in advance and then adding the monomer mixture to the suspension.
[0037] Emulsifier can be for example polyvinyl alcohol, or other surfactants. As other surfactants, salts of fatty acids such as myristic acid, palmitic acid, oleic acid, linolenic acid, alkylbenzene sulfonates such as sodium dodecylbenzene sulfonate, higher alcohol sulfate salts such as sodium lauryl sulfate, higher phosphate salts such as sodium alkyl phosphate, alkyl sulfosuccinates, polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene alkylphenol ethers such as polyoxyethylene nonylphenyl ether, polyoxyethylene alkyl esters, polyoxyethylene sorbitan alkyl esters, polyoxyethylene polyoxypropylene glycol, and, polyethylene glycol monostearate can be enumerated. When using these surfactants as emulsifiers, compared with the situation of using polyvinyl alcohol as emulsifier, there is a tendency that toluene insoluble components further decrease.
[0038] If necessary, the monomer mixture may further contain the above-mentioned monomers constituting the acrylic rubber (except for gaseous monomers such as ethylene) in addition to ethyl acrylate and n-butyl acrylate.
[0039] A pH adjuster may be further added to the suspension. The pH adjuster may be, for example, an alkali metal salt such as sodium acetate, sodium hydroxide, potassium hydroxide, sodium phosphate, sodium citrate, etc., preferably sodium acetate. The amount of the pH adjuster added may be, for example, 0.1 parts by mass or more, or 5 parts by mass or less, relative to 100 parts by mass of the total amount of monomers constituting the acrylic rubber.
[0040] The polymerization initiator may be, for example, an azo compound such as azobisisobutyronitrile, an organic peroxide such as tert-butyl hydroperoxide, cumene hydroperoxide, benzoyl peroxide, or an inorganic peroxide such as sodium persulfate, ammonium persulfate, preferably tert-butyl hydroperoxide. The amount of the polymerization initiator added may be, for example, 0.01 parts by mass or more, or 2 parts by mass or less, relative to 100 parts by mass of the total amount of monomers constituting the acrylic rubber.
[0041] Based on the total amount of the acrylic rubber, from the viewpoint of improving the bending fatigue resistance of the cross-linked product, the content of the toluene-insoluble components in the acrylic rubber obtained as above is 5% by mass or less, and from the viewpoint of further improving the bending fatigue resistance of the cross-linked product, it is preferably 4.5% by mass or less, more preferably 4% by mass or less, further preferably 3.5% by mass or less, and particularly preferably 3% by mass or less. From the viewpoint of improving the moldability of the cross-linked product, based on the total amount of the acrylic rubber, the content of the toluene-insoluble components in the acrylic rubber is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, further preferably 1% by mass or more, and particularly preferably 1.5% by mass or more.
[0042] The content of the toluene-insoluble component in the acrylic rubber is measured as follows.
[0043] Accurately weigh 1g of acrylic rubber, dissolve it in 100mL of toluene at a temperature of 25°C for 48 hours, and then transfer the solution to a 250mL centrifuge tube with a pre-measured mass (set as X (g)). Next, use an angle rotor with a maximum centrifugal radius of 13.8cm to centrifuge the solution at a temperature of 10°C, 8500rpm, and 60 minutes, and then remove non-precipitates by decantation. Dry the precipitate in the centrifuge tube in a vacuum dryer at a temperature of 70°C for 24 hours, and measure the mass of the dried centrifuge tube (set as Y (g)). Based on the measured X and Y, calculate the toluene insoluble component by the following formula.
[0044] Toluene insoluble content (mass %) = (YX) × 100
[0045] As described above, the toluene-insoluble components in the acrylic rubber can be adjusted by the mixing order when the monomer mixture and the aqueous solution of the emulsifier are mixed to prepare the suspension. In addition, the toluene-insoluble components in the acrylic rubber can also be adjusted by the mass ratio of the content of ethyl acrylate in the monomer units contained in the acrylic rubber to the content of n-butyl acrylate. The larger the mass ratio, the less the toluene-insoluble components in the acrylic rubber tend to be.
[0046] The Mooney viscosity of the acrylic rubber may be, for example, 10 or more, 20 or more, or 30 or more, or 70 or less, 60 or less, or 50 or less. The Mooney viscosity of the acrylic rubber is a value measured by the method specified in JIS K6300, specifically, a value measured 4 minutes after the start of rotation after preheating at 100° C. for 1 minute using an L-type rotor.
[0047] The acrylic rubber described above can be used as a rubber composition in combination with other components as needed. That is, another embodiment of the present invention is a rubber composition containing the acrylic rubber (and other components used as needed). Based on the total amount of the rubber composition, the content of the acrylic rubber can be, for example, 50% by mass or more, 55% by mass or more, or 60% by mass or more, and can be 90% by mass or less.
[0048] Examples of other components that may be contained in the rubber composition include fillers, lubricants, antioxidants, surfactants, crosslinking agents, and crosslinking accelerators.
[0049] Examples of the filler include carbon black, silica, talc, and calcium carbonate. The content of the filler may be, for example, 30 parts by mass or more, or 100 parts by mass or less, relative to 100 parts by mass of the acrylic rubber.
[0050] Examples of the lubricant include liquid paraffin, stearic acid, stearylamine, fatty acid zinc, fatty acid esters, and organosilicone. The content of the lubricant may be, for example, 0.1 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the acrylic rubber.
[0051] Examples of the antioxidant include aromatic amine compounds and phenol compounds. The content of the antioxidant may be, for example, 0.1 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the acrylic rubber.
[0052] Examples of the surfactant include alkyl sulfate ester salts. The content of the surfactant may be, for example, 0.1 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the acrylic rubber.
[0053] Examples of the crosslinking agent include imidazole compounds and diamine compounds. The content of the crosslinking agent may be, for example, 0.1 parts by mass or more and 10 parts by mass or less relative to 100 parts by mass of the acrylic rubber.
[0054] When the rubber composition contains a crosslinking agent, a crosslinking accelerator is preferably used. Examples of the crosslinking accelerator include trimethylthiourea compounds, phenothiazine compounds, and guanidine compounds. The content of the crosslinking accelerator may be, for example, 0.1 parts by mass or more, or 10 parts by mass or less, relative to 100 parts by mass of the acrylic rubber.
[0055] The rubber composition is suitable for use in a cross-linked state (as a cross-linked product). That is, another embodiment of the present invention is a cross-linked product of the above-mentioned rubber composition. The cross-linked product can be obtained by cross-linking the rubber composition. In the cross-linked product, the acrylic rubbers are cross-linked with each other using the cross-linking points (cross-linking sites) of the cross-linking point monomer contained as a monomer unit in the acrylic rubber. When the rubber composition contains a cross-linking agent, the cross-linking of the acrylic rubbers is further formed with the cross-linking agent.
[0056] The method for cross-linking the rubber composition may be a known method, and may include, for example, a first cross-linking step of heating and pressurizing the rubber composition; and a second cross-linking step of further heating the rubber composition after the first cross-linking step.
[0057] In the first crosslinking step, the heating temperature may be, for example, 150° C. or higher but 220° C. or lower. The pressure during pressurization may be, for example, 0.4 MPa or higher but 20 MPa or lower. The heating and pressurization time may be, for example, 5 minutes or higher but 2 hours or lower.
[0058] In the second cross-linking step, the heating temperature may be, for example, 150° C. or higher and 220° C. or lower. The heating time may be, for example, 30 minutes or higher and 24 hours or lower.
[0059] The crosslinked product of the rubber composition is suitable for use as a sealing component such as a rubber hose, a gasket, and a sealing packing, and is particularly suitable for use in a rubber hose. That is, another embodiment of the present invention is a rubber hose or a sealing component comprising the crosslinked product, preferably a rubber hose comprising the crosslinked product. The rubber hose and the sealing component may be composed of only the crosslinked product of the rubber composition, or may include the crosslinked product and other components.
[0060] Examples of the rubber hose include transmission oil cooler hoses, engine oil cooler hoses, air duct hoses, turbo intercooler hoses, hot air hoses, radiator hoses, power steering hoses, fuel system hoses, and exhaust system hoses for automobiles, construction machinery, hydraulic equipment, and the like.
[0061] Examples of sealing components include engine top cover gaskets, oil pan gaskets, oil seals, lip seal packages, O-rings, transmission gaskets, crankshafts, camshaft gaskets, valve stems, power steering belt cover seals, constant velocity joint boot materials, and rack and pinion boot materials.
[0062] Example
[0063] Hereinafter, the present invention will be described in more detail using examples, but the present invention is not limited to these examples.
[0064] <Examples 1 to 5>
[0065] Into a pressure-resistant reaction vessel with an internal volume of 40 liters, 11 kg of a monomer mixture containing the monomers shown in Table 1 (excluding ethylene), 17 kg of a 4% by mass aqueous solution of polyvinyl alcohol, and 22 g of sodium acetate were added, and the mixture was fully mixed in advance by a stirrer to prepare a uniform suspension. After the air in the upper part of the container was replaced with nitrogen, ethylene was pressed into the upper part of the container at a pressure of 3 MPa (except Example 5). Stirring was continued, and after the container was kept at 55°C, 2 liters of tert-butyl hydroperoxide aqueous solution (0.25% by mass) were added to start polymerization. The temperature in the container was maintained at 55°C, and the reaction was terminated after 6 hours. 7 liters of sodium borate aqueous solution (3.5% by mass) were added to the obtained copolymer to solidify the copolymer. After the solidified copolymer was washed with water, it was dehydrated and dried to obtain an acrylic rubber.
[0066] <Comparative Examples 1 and 2>
[0067] Into a pressure-resistant reaction vessel with an internal volume of 40 liters, 17 kg of a 4% aqueous solution of polyvinyl alcohol and 22 g of sodium acetate were added, and the mixture was fully mixed in advance by a stirrer to prepare a uniform suspension. After the air in the upper part of the container was replaced with nitrogen, ethylene was pressed into the upper part of the container at a pressure of 3 MPa. Stirring was continued, and after the container was kept at 55°C, 11 kg of a monomer mixture containing the monomers shown in Table 1 (excluding ethylene) and 2 liters of an aqueous solution of tert-butyl hydroperoxide (0.25% by mass) were added over 6 hours to start polymerization. The temperature in the container was kept at 55°C, and the reaction was terminated after 6 hours. 7 liters of an aqueous sodium borate solution (3.5% by mass) were added to the obtained copolymer to solidify the copolymer. After the solidified copolymer was washed with water, it was dehydrated and dried to obtain an acrylic rubber.
[0068] <Comparative Example 3>
[0069] Into a pressure-resistant reaction vessel with an internal volume of 40 liters, 1 kg of a monomer mixture containing the monomers shown in Table 1 (excluding ethylene), 17 kg of a 4% aqueous solution of polyvinyl alcohol, and 22 g of sodium acetate were added, and mixed thoroughly in advance by a stirrer to prepare a uniform suspension. After replacing the air in the upper part of the container with nitrogen, ethylene was pressed into the upper part of the container at a pressure of 3 MPa. Stirring was continued, and after the container was kept at 55°C, 10 kg of a monomer mixture containing the monomers shown in Table 1 (excluding ethylene) and 2 liters of an aqueous solution of tert-butyl hydroperoxide (0.25% by mass) were added over 6 hours to start polymerization. The temperature in the container was kept at 55°C, and the reaction was terminated after 6 hours. 7 liters of an aqueous sodium borate solution (3.5% by mass) were added to the obtained copolymer to solidify the copolymer. After the solidified copolymer was washed with water, it was dehydrated and dried to obtain an acrylic rubber.
[0070] The composition of the monomer units contained in the obtained acrylic rubber is shown in Table 1. In addition, the content of the monomer units was measured by nuclear magnetic resonance spectroscopy.
[0071] Furthermore, the content of the toluene-insoluble component in the obtained acrylic rubber and the Mooney viscosity ML (1+4) 100° C. of the acrylic rubber were measured. The results are shown in Table 1.
[0072] The toluene insoluble component is measured by the following method. That is, first, accurately weigh 1 g of acrylic rubber, dissolve it in 100 mL of toluene at a temperature of 25°C for 48 hours, and then transfer the dissolved solution to a 250 mL centrifuge tube whose mass (set as X (g)) has been measured in advance. Next, use an angle rotor with a maximum centrifugal radius of 13.8 cm, centrifuge the dissolved solution at a temperature of 10°C, 8500 rpm, and 60 minutes, and then remove non-precipitates by decantation. Dry the precipitate in the centrifuge tube in a vacuum dryer at a temperature of 70°C for 24 hours, and measure the mass of the dried centrifuge tube (set as Y (g)). Based on the measured X and Y, the toluene insoluble component is calculated by the following formula.
[0073] Toluene insoluble content (mass %) = (YX) × 100
[0074] The Mooney viscosity ML (1+4) at 100° C. is measured according to the method specified in JIS K6300.
[0075] Next, 100 parts by mass of each of the obtained acrylic rubbers, 45 parts by mass of a filler (carbon black (SEAST SO manufactured by TOKAI CARBON CO., LTD.)), 1 part by mass of a lubricant a (liquid paraffin (HICALL K-230 manufactured by Kaneda CO., LTD.)), 1 part by mass of a lubricant b (paraffin (paraffin 135F manufactured by NIPPON SEIRO CO., LTD.)), 1 part by mass of a lubricant c (stearic acid (manufactured by NOF Corporation)), 0.3 part by mass of a lubricant d (stearylamine (FARMIN 80 manufactured by Kao Corporation)), 0.5 part by mass of an antioxidant a (4,4'-bis(α,α-dimethylbenzyl)diphenylamine (Naugard #445 manufactured by Addivant)), 0.5 part by mass of an antioxidant b (N-phenyl-N'-isopropyl-p-phenylenediamine (NOCRAC manufactured by Ouchi Shinko Chemical Industry Co., Ltd.) 810-NA)), 1 mass part of a mold release agent (a phosphate compound (MOLD WIZ INT-21G manufactured by Basque Industries)), 0.5 mass part of a crosslinking agent (hexamethylenediamine carbamate (Diak#1 manufactured by Du Pont)), and 1.5 mass parts of a crosslinking accelerator (XLA-60 manufactured by LANXESS) were kneaded on an 8-inch open mill to obtain a rubber composition.
[0076] The obtained rubber composition was formed into a sheet with a thickness of 2.4 mm, and then heated and pressed at 170° C. and 10 MPa for 20 minutes in a press vulcanizer. Next, it was heated at 170° C. for 4 hours in a Gir oven to obtain a crosslinked rubber composition.
[0077] (Evaluation of tensile strength of cross-linked product)
[0078] The tensile strength of the cross-linked product was measured in accordance with JIS K6251:2010.
[0079] (Evaluation of Bending Fatigue Resistance of Cross-linked Product)
[0080] According to JIS-K6260:2010, the number of bends until a 0.5 mm crack is generated in the crosslinked product is measured at 23°C and 100°C. The number of bends is the average value of the results obtained by performing the same measurement on 5 samples. The greater the number of bends, the better the bending fatigue resistance.
[0081] (Evaluation of cold resistance of cross-linked products)
[0082] T100 of the cross-linked product is measured according to JIS K6261: 2006. T100 is a temperature at which a value is 100 times the value of the specific modulus of the cross-linked product at 23° C. The lower T100 is, the better the cold resistance is.
[0083] (Evaluation of Formability)
[0084] The obtained rubber composition was molded into a tube (inner diameter: 9 mm, outer diameter: 14 mm) using a rubber single-screw extruder (screw diameter: 50 mm), screw rotation speed: 20 rpm, nozzle temperature: 110°C, barrel temperature: 90°C, hopper temperature: 70°C. The mass W (g), length L (cm) in the extrusion direction, and density ρ (g / cm) of the obtained tube were measured. 3 ), and the die swell DS (%) was calculated using the following formula.
[0085] DS=(W / LρS0-1)×100
[0086] Where S0 is the area of the mold (cm 2 ). The smaller the mold expansion, the better the moldability.
[0087] Table 1 shows the above evaluation results.
[0088] [Table 1]
[0089]
Claims
1. Acrylic rubber comprising ethyl acrylate, n-butyl acrylate, ethylene and a cross-linking monomer having a carboxyl group as monomer units, and comprising a toluene-insoluble component, Based on the total amount of the monomer units, the content of ethyl acrylate is 74-90% by mass, the content of n-butyl acrylate is 10-22% by mass, the content of ethylene is 1-3% by mass, and the content of the cross-linking point monomer is 1-3% by mass. The mass ratio of the content of the ethyl acrylate to the content of the n-butyl acrylate is 4.1 or more and 8 or less, The Mooney viscosity of the acrylic rubber is 50 or less, The content of the toluene-insoluble component is 1.5% by mass or more and 5% by mass or less based on the total amount of the acrylic rubber. The Mooney viscosity of the acrylic rubber is a value measured according to the method specified in JIS K6300, specifically, a value measured 4 minutes after the start of rotation after preheating at 100° C. for 1 minute using an L-type rotor. 2 . The acrylate rubber according to claim 1 , which contains no methacrylate as a monomer unit. 3 . The acrylic rubber according to claim 1 , comprising only the ethyl acrylate, the n-butyl acrylate, ethylene, and a cross-linking point monomer having a carboxyl group as monomer units. 4 . A rubber composition comprising the acrylic rubber according to claim 1 .
5. A cross-linked product of the rubber composition according to claim 4.
6. A rubber hose comprising the cross-linked product according to claim 5.
Citation Information
Patent Citations
Acrylic rubber composition and rubber crosslinked product
JP2012211239A
Tire bladder
CN103328172A
Acrylic rubber
CN110291118A
Acrylic rubber, crosslinkable rubber composition, and cured rubber product
CN114174355A
Acrylate rubber, rubber composition and crosslinked product thereof, rubber hose, and sealing member
CN114502642A